Peculiarity of mathematical objects. Function - Kavaliauskas , Algis (Lietuvos matematikos rinkinys, 2008)
The article deals with some possibledefinitionsof function. Shortagesof function definitionused at schools are discussed. Some concrete examples of improper use of definitions like function and expression, function and its graph are analyzed. Furthermore, some features of recording dimensional and not dimensional variables and their functions are discussed.